2016
DOI: 10.1016/s0140-6736(16)30825-x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and supportive care with or without whole brain radiotherapy in treating patients with non-small cell lung cancer with brain metastases unsuitable for resection or stereotactic radiotherapy (QUARTZ): results from a phase 3, non-inferiority, randomised trial

Abstract: SummaryBackgroundWhole brain radiotherapy (WBRT) and dexamethasone are widely used to treat brain metastases from non-small cell lung cancer (NSCLC), although there have been no randomised clinical trials showing that WBRT improves either quality of life or overall survival. Even after treatment with WBRT, the prognosis of this patient group is poor. We aimed to establish whether WBRT could be omitted without a significant effect on survival or quality of life.MethodsThe Quality of Life after Treatment for Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
424
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 612 publications
(437 citation statements)
references
References 42 publications
8
424
2
3
Order By: Relevance
“…The factors including gender, age, radiotherapy dose in whole brain and pathological grading have no significant influence on survival. The ECOG score is higher, the poorer the prognosis will be, which is to correspondence with the previous reports [26][27][28]. The radiotherapy dose in intracranial metastases is positively related with the prognosis.…”
Section: It Is Recommended By National Comprehensive Cancersupporting
confidence: 90%
See 1 more Smart Citation
“…The factors including gender, age, radiotherapy dose in whole brain and pathological grading have no significant influence on survival. The ECOG score is higher, the poorer the prognosis will be, which is to correspondence with the previous reports [26][27][28]. The radiotherapy dose in intracranial metastases is positively related with the prognosis.…”
Section: It Is Recommended By National Comprehensive Cancersupporting
confidence: 90%
“…Therefore, whole brain radiotherapy is controversial at present. Especially for those patients with poor general medical condition, best support care has similar efficacy as whole brain radiotherapy [5,[28][29][30]. It was revealed that radiotherapy times are negatively related with the prognosis.…”
Section: It Is Recommended By National Comprehensive Cancermentioning
confidence: 99%
“…27 Observation may be appropriate for patients with small, asymptomatic brain metastases, particularly if they have a short life expectancy. 28 Neurosurgical resection of a brain metastasis may be advised for larger, symptomatic brain metastases, or if there are no other easily biopsied lesions for pathologic confirmation in patients. Systemic therapy can be considered for small, asymptomatic brain metastases if the systemic therapy in consideration has some known activity in the brain.…”
Section: Neurooncologymentioning
confidence: 99%
“…According to Table 5, patients with brain metastases are not receiving anticancer therapy only if they have progression of the disease after receiving several types of anticancer therapy and them performance status stay poor after adequate supportive care [19].…”
Section: Cancer Management and Therapymentioning
confidence: 99%